Management of chronic pelvic pain in patients with endometriosis - Negrón Rodríguez, José (2016)
Endometriosis, a disease of unknown etiology, causes significant morbidity in reproductive-age women as a result of chronic pelvic pain. Several mechanisms could explain the relationship between endometriosis and pelvic pain, with potential therapeutic targets. Endometriosis-associated pain can be treated medically or with surgery either conservative or radical. Medical therapies induce a steady hormonal status unfavorable for endometriosis development. Surgical therapies for endometriosis-associated pain include conservative treatments such as removal of endometriotic implants, nodules, and adhesions with restoration of normal pelvic anatomy. Radical surgery involves both removal of the uterus with or without the ovaries in patients who have completed childbearing, and removal of all residual pelvic lesions.